PERPUTARAN UANG DI INDONESIA: PERAN UANG ELEKTRONIK, VOLUME TRANSAKSI ELEKTRONIK DAN JUMLAH MESIN EDC - Muhammad Fadlillah Fauzukhaq; Luthfan Darma Prasetia; Akhmad Akbar (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2019)
The purpose of this study is to analyze the effect of theuse of electronic money which includes the amount of electronic money in circulation, the volume of electronicmoney transactions and the number of electronic money EDC machines on the velocity of moneyin Indonesia. The data used in the study are secondary data from the Central Statistics Agency (BPS) and the Central Bank (BI) and analyzed by linear regression. The results showed that the amount of electronic money incirculation and the number of Electronic Data Capture (EDC) Machines had a significant effect on the velocity of money in Indonesia, while the volume of electronic money transaction sdid not have a significant effect on the velocity of money in Indonesia.